2010
DOI: 10.1001/jama.2010.607
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Therapy for Children With Tourette Disorder

Abstract: Context Tourette disorder is a chronic and typically impairing childhood-onset neurological condition. Antipsychotic medications, the first-line treatments for moderate to severe tics, are often associated with adverse effects. Behavioral interventions, although promising, have not been evaluated in large-scale controlled trials. Objective To determine the efficacy of a comprehensive behavioral intervention for reducing tic severity in children and adolescents. Design, Setting, Participants Randomized, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
588
6
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 625 publications
(627 citation statements)
references
References 41 publications
(37 reference statements)
25
588
6
8
Order By: Relevance
“…A checklist of adverse events was developed for one of the trials [20]. In another trial the therapists asked about adverse events each session [21]. The participants in yet another trial, spanning over two years, were assessed for relapse and major incidents every month [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A checklist of adverse events was developed for one of the trials [20]. In another trial the therapists asked about adverse events each session [21]. The participants in yet another trial, spanning over two years, were assessed for relapse and major incidents every month [23].…”
Section: Discussionmentioning
confidence: 99%
“…Four reports provided a complete report of occurring adverse events as well as the methods used for collecting these data [20][21][22][23]. In a trial of cognitivebehavioral therapy for posttraumatic stress disorder (PTSD) in children [20], an 8-item checklist was designed to measure adverse events.…”
Section: Reporting Of Harmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have demonstrated tic-suppressing efficacy as a form of cognitive behavioral therapy called "habit reversal", which involves training patients to self-monitor their tics and premonitory sensations, and to respond to them by performing a voluntary behavior that is physically incompatible with the tic [9]. Potential shortcomings of habit reversal therapy are that it must be administered by a specially trained therapist so it is not widely available, it is time-consuming, and its longterm benefits have not been examined.…”
Section: Cognitive Behavioral Therapy For Ticsmentioning
confidence: 99%
“…In more recent years, the conceptualization of Tourette disorder as a biologically based condition that is highly influenced by psychocontextual factors has emerged, given the growing research demonstrating the efficacy of behavioral approaches for the treatment of tics. 11 Of course, the efficacy of a particular mode of treatment should not be viewed as evidence of a disorder's cause, but with the discovery that different modalities of treatment could be effective, the broad factors seen as impacting symptoms have changed, and this has resulted in various approaches to classification. Diagnostically, tics were included in the first version of the DSM, though they were categorized as ''neurotic traits'' and viewed as a symptom of an underlying neurosis.…”
Section: Historical Backgroundmentioning
confidence: 99%